IMPLEMENTATION OF DEVOPS METHOD FOR AUTOMATION OF SERVER MANAGEMENT USING ANSIBLE - Khumaidi, Ali (Jurnal Transformatika, 2021)
The Development and Operations (DevOps) method is develops tasks that are operationalized by IT staff including server management. DevOps is a server, coding, and tester bridge so that it can be activated automatically so that the programmer does not need to do it repeatedly. Server management is still mostly done manually by doing repetitive settings on one server and another server so that it is inefficient and requires a relatively long time, the solution by adding several employees will increase the work of making users and user management on all servers, the occurrence of human errors and burdens costs for the company. Ansible is one type of configuration management tools that can be used for the infrastructure management process from a manual program to an automatic. In this study the implementation and testing of Ansibel was done in server management. Ansibel can configure and manage user account settings on all servers automatically.
Keywords: Ansible; DevOps; Management Server; SSH; User Account